Recurrent and Bilateral Peritonsillar Abscess: A Rare Cause of Upper Airway Obstruction - Leman Akcan Yıldız; Dilara Ünal; Özlem Tekşam (Galenos Yayinevi, 2021)
Peritonsillar abscess is a rare but serious complication of acute tonsillitis. Bilateral peritonsillar abscess must be diagnosed and treated promptly because it can cause upper airway obstruction. In this case report, we report a patient with bilateral peritonsillar abscess, who presented with a sore throat, fever and difficulty swallowing and underwent unilateral peritonsillar abscess drainage one year ago.